1996
DOI: 10.1097/00006123-199607000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Coma Scale in the Prediction of Outcome after Early Aneurysm Surgery

Abstract: The GCS proved useful in the preoperative evaluation of patients with SAH, in terms of outcome prediction. It is suggested that the SAH scale proposed by the World Federation of Neurosurgical Societies be reexamined, because differences in outcomes were not clear between the GCS scores of 13 and 12 or between those of 7 and 6, in which Grades III and IV and Grades IV and V are differentiated in the scale, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 12 publications
4
49
0
1
Order By: Relevance
“…The JCS is widely used for the assessment of impaired consciousness in patients with SAH in Japan. 2,12,14,25,32 Although the JCS cannot assess neurological impairment other than diminished consciousness, the JCS score on admission had the greatest impact on the outcomes of patients with SAH. 9 In addition, JCS scores have been reported to correlate with stroke outcomes.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JCS is widely used for the assessment of impaired consciousness in patients with SAH in Japan. 2,12,14,25,32 Although the JCS cannot assess neurological impairment other than diminished consciousness, the JCS score on admission had the greatest impact on the outcomes of patients with SAH. 9 In addition, JCS scores have been reported to correlate with stroke outcomes.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…29 Therefore, we believe that the JCS is sufficient for clinical grade assessment in patients with SAH. However, as an increasing number of stroke researchers have used JCS scores in recent Japanese DPC database studies, 2,9,12,14,25,30,33 it may be necessary to compare the JCS scoring system with more typical grading scales. Third, the DPC database includes information collected only during hospitalization; thus, we were unable to evaluate long-term outcomes.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…The GCS initially intended to assess the level of consciousness after head injury in neurosurgical intensive care unit is widely used in neurological patients beyond the original intentions in the context of outcome prediction (e.g., [11]. ), neurosurgical prognostic indicator (e.g., [12]. ), cerebral dysfunction measurement (e.g., [13].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies of the JCS in patients with aneurysmal subarachnoid hemorrhage reported that the preoperative level of consciousness as measured by JCS is well correlated with the outcome. 6,30) However, the validity of this scale for head injury has not been clarified. CT is widely available and less expensive in Japan (1/2 to CT: computed tomography, GCS: Glasgow Coma Scale.…”
Section: Introductionmentioning
confidence: 99%